KEINSIANISM AND PROGRAMS OF SOCIO-ECONOMIC AND POLITICAL TRANSFORMATION IN POLAND (1990-1995) (Economic journal of Lesya Ukrainka Volyn National University, 2019)
The main privatisation programmes of reforming the Polsh Economy in the period of transition to the market economy are analysed in this artikle. Tge analysis is made on the basis of rich documentary material, statistic data (Ukrainian and Polish ones) It is stressed that the privatisation programmes originated from the "Baltserovych Programe" and "Kolodko Plan "Strategy from Poland". These two documents were used as the basic ones in the process of composing the privatіsatіon programme. According to this programme the freedom of business and equality of different forms of property were secured legislatively. They provided the judicial basis tor the reforming ot the national economy and accession of Poland to the Europian economic organisations and other associations. Having set specific goals, Poland immediately began to systematically transform its economy, legal framework and many state institutions in line with EU standards. Taking into account the Keynesian model of state interference in the economy, unlike other Eastern European countries, the Polish transformation and integration processes have been developing consistently and dynamically: Poland has entered into negotiations on economic integration with the European Union immediately after the beginning of economic liberalization in 1990. In the country, systemic transformations of the economy, legal framework and many state institutions into compliance with EU standards began. Socio-economic and political privatization programs, including Baltserovich's Plan, Kolodko Plan, and the Strategy for Poland, legislatively established the freedom of entrepreneurship and the equality of different forms of ownership, created the legal basis for reforming the economy and Poland's accession to the European organizations: March 12 1999 in NATO, May 1, 2004 in the European Union.
Keywords: economy, enterprise, market system, private property, stock exchange, privatisation, economic positing, competition, transformation, transition